Novel application of mixed hydrotropic solubilization technique in the formulation and evaluation of hydrotropic solid dispersion of aceclofenac - Maheshwari, Rajesh Kumar; Indurkhya, Arpna (Asian Journal of Pharmaceutics (AJP), 2014)
In the present investigation, newly developed mixed hydrotropic solid dispersion (HSD) technology precludes the use of organic solvent and also decreases the individual concentration of hydrotropic agents, simultaneously decreasing their toxic potential. ‘Mixed-hydrotropic solubilization’ technique is the phenomenon to increase the solubility of poorly water- soluble drugs in the aqueous solution containing blends of hydrotropic agents, which may give synergistic enhancement effect on solubility of poorly water-soluble drugs and to reduce concentrations of each individual hydrotropic agent to minimize their toxic effects due to high concentration of hydrotropic agents. Maheshwari has made HSD of paracetamol using urea. In the present study, the aqueous solution of hydrotropic blend (20% urea and 10% sodium citrate) has been found to increase aqueous solubility of poorly water-soluble drug, aceclofenac. This mixedhydrotropic blend was used to prepare solid dispersion of aceclofenac. The prepared solid dispersions have been characterized by IR and XRD studies. They have been studied for dissolution rate enhancement effect. The prepared solid dispersions were found very stable (chemically).